Effect of brief self-regulation couple therapy in conflict resolution and couple burnout - Leila Sepehrian; Farideh Dokanheeifard (Gonabad University of Medical Sciences, 2017)
Unconstructive conflict resolution and couple burnout have a negative impact on quality of marital life. Brief self-regulation couple therapy is one of the effective approaches in transmission teachings and marital skills to couples. The aim of the current research was to investigate the effect of brief self-regulation couple therapy in conflict resolution and couple burnout among troubled couples. This was a quasi-experimental research that employed a pre and posttest design with a control group. The statistical population comprised the couples who referred to the health houses of Tehran city. The couples were selected according to convenience sampling method. Thus, upon an announcement, a sample of 30 couples who were eligible for the study and received lower scores in communicational conflict resolution scale and couple burnout inventory was selected as participants. They were assigned into two groups of experimental and control (n=15 in each group). The experimental group participated in 8 sessions of brief self-regulation couple therapy and the control group received no treatment. The results showed that there were significant differences in the posttest scores between the experimental and control groups, indicating that brief self-regulation couple therapy could significantly improve conflict resolution and reduce couple burnout among couples. Thus, interventions based on brief self-regulation couple therapy could be useful in improving conflict resolution and reducing couple burnout of couples.